Investing in the Afterlife as a Bridge to Financial Freedom (Study on Pekalongan City BWI Representative) - Hidayatul Sibyani; Fitri Mukarromah; Hendri Hermawan Adinugraha; Muhammad Shulthoni (AL- IKTISAB Journal of Islamic Economic Law, 2022)
Most people believe that financial independence has a large amount of money, goods, and assets. What is meant by financial independence is not only having a lot of money, goods, and assets, but the magnitude is in the financial goals that must be met. However, people who care about the hereafter will assume that whatever they do is compatible with happiness in the afterlife. This research uses empirical studies and descriptive analysis in the form of a mixture of field research and library research conducted using qualitative research strategies. This research uses primary data obtained from interviews and direct observations at the Indonesian Waqf Board of Pekalongan city, as well as secondary data obtained from publications, books, internet, previous research, and other relevant reference sources. The technique used in primary data collection is through interviews with related parties and direct observation in the field. The results of this research are as a Muslim who is oriented to the afterlife, there is awareness for Muslims who have assets that are considered valuable and have been calculated when the object is donated will not harm their family as Islamic teachings that cash waqf. A beloved treasure is a charity that will not harm his family break up because it will help him when experiencing difficulties in the hereafter and the urgency of this waqf, the property belongs to Allah and must be returned to Allah for the benefit of others. All activities are fully entrusted to the head of BWI Pekalongan city.Kebanyakan orang percaya bahwa kemandirian finansial memiliki sejumlah besar uang, barang, dan aset. Yang dimaksud dengan kemandirian finansial bukan hanya memiliki banyak uang, barang, dan aset, tetapi besarnya ada pada tujuan finansial yang harus dipenuhi. Namun, orang-orang yang peduli pada akhirat akan menganggap bahwa apapun yang mereka lakukan itu sesuai dengan kebahagiaan di akhirat. Penelitian ini menggunakan studi empiris dan analisis deskriptif berupa campuran penelitian lapangan dan penelitian kepustakaan yang dilakukan dengan menggunakan strategi penelitian kualitatif. Penelitian ini menggunakan data primer yang diperoleh dari wawancara dan observasi langsung di Badan Wakaf Indonesia kota Pekalongan, serta data sekunder yang diperoleh dari publikasi, buku, internet, penelitian terdahulu, dan sumber referensi lain yang relevan. Teknik yang digunakan dalam pengumpulan data primer adalah melalui wawancara dengan pihak terkait dan observasi langsung di lapangan. Hasil dari penelitian ini adalah sebagai seorang Muslim yang berorientasi pada akhirat, ada kesadaran bagi umat Islam yang memiliki harta yang dianggap berharga dan telah diperhitungkan ketika benda tersebut dihibahkan tidak akan merugikan keluarganya sebagaimana ajaran Islam yaitu wakaf uang. Harta yang dicintai adalah sedekah yang tidak akan merugikan keluarganya karena akan membantunya ketika mengalami kesulitan di akhirat, dan pentingnya wakaf ini, harta itu milik Allah dan harus dikembalikan kepada Allah untuk kepentingan orang lain. Seluruh kegiatan dipercayakan sepenuhnya kepada kepala BWI kota Pekalongan.